2022
DOI: 10.3390/biology11111583
|View full text |Cite
|
Sign up to set email alerts
|

Negative Magnetic Sorting Preserves the Functionality of Ex Vivo Cultivated Non-Adherent Human Monocytes

Abstract: Background: Monocyte-derived macrophages or dendritic cells are of increasing interest for cellular therapeutic products to treat inflammation-related diseases and cancer. However, the isolation method and the culture conditions applied influence the functionality of cells. For some approaches, the adhesion-induced differentiation into macrophages must be prevented to maintain functions attributed to circulating monocytes. The effects of the isolation method on the functionality of non-adherent peripheral mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Although an enrichment for CD14 + monocytes by magnetic/fluorescence-activated cell sorting (MACS) might be reasonable to further enhance osteoclast yields, a priori positive selection for CD14 + precursors might affect cell differentiation due to the induction of different cellular phenotypes and the presence of residual beads in the culture system [ 32 ]. Indeed, Hornschuh and colleagues reported a significant decrease in monocyte functionality, cytokine release and viability after MACS-based CD14 sorting compared to negatively selected cells [ 33 ]. However, another study observed that negatively selected monocytes might be contaminated with high numbers of platelets and skewed towards a M2 polarization [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although an enrichment for CD14 + monocytes by magnetic/fluorescence-activated cell sorting (MACS) might be reasonable to further enhance osteoclast yields, a priori positive selection for CD14 + precursors might affect cell differentiation due to the induction of different cellular phenotypes and the presence of residual beads in the culture system [ 32 ]. Indeed, Hornschuh and colleagues reported a significant decrease in monocyte functionality, cytokine release and viability after MACS-based CD14 sorting compared to negatively selected cells [ 33 ]. However, another study observed that negatively selected monocytes might be contaminated with high numbers of platelets and skewed towards a M2 polarization [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…For maturation, CD34 + cells take 7-12 days to differentiate using granulocyte-macrophage colony-stimulating factor (GM-CSF), IL-4, and stronger pro-inflammatory cytokines such as stem cell factor (SCF), FMS-like tyrosine kinase 3 (Flt3L), thrombopoietin (TPO), TNF-α, IL-3, IL-4, and IL-6. 10,13,17,18 Meanwhile, monocytes only take 5-6 days for maturation. [19][20][21][22][23] There are approximately 5.28% and 7.91% monocytes that can be isolated from adult PB and UCB, respectively.…”
Section: Monocytes Sourcesmentioning
confidence: 99%
“…However, the potency to attach, migrate, and releasing cytokines are lower than negatively selected monocytes. 17,28 This may be because of interaction between antibody and CD14 indicating "danger signal", causing early maturation. In addition, by flowing through the magnetic field, the monocytes can shrink and lead to cell death.…”
Section: Magnetic Sortingmentioning
confidence: 99%
See 2 more Smart Citations